Opportunities in Reform: Bioethics and Mental Health Ethics - Williams, Arthur Robin (Bioethics, 2016)
Last year marks the first year of implementation for both the Patient Protection and Affordable Care Act and the Mental Health Parity and Addiction Equity Act in the United States. As a result, healthcare reform is moving in the direction of integrating care for physical and mental illness, nudging clinicians to consider medical and psychiatric comorbidity as the expectation rather than the exception. Understanding the intersections of physical and mental illness with autonomy and self-determination in a system realigning its values so fundamentally therefore becomes a top priority for clinicians. Yet Bioethics has missed opportunities to help guide clinicians through one of medicine's most ethically rich and challenging fields. Bioethics' distancing from mental illness is perhaps best explained by two overarching themes: 1) An intrinsic opposition between approaches to personhood rooted in Bioethics' early efforts to protect the competent individual from abuses in the research setting; and 2) Structural forces, such as deinstitutionalization, the Patient Rights Movement, and managed care. These two themes help explain Bioethics' relationship to mental health ethics and may also guide opportunities for rapprochement. The potential role for Bioethics may have the greatest implications for international human rights if bioethicists can re-energize an understanding of autonomy as not only free from abusive intrusions but also with rights to treatment and other fundamental necessities for restoring freedom of choice and self-determination. Bioethics thus has a great opportunity amid healthcare reform to strengthen the important role of the virtuous and humanistic care provider.